Comparison of Blood Cholesterol Profiles Before and After The Measurements of Maximum Aerobic Capacity (VO2max) - AR SHADIQIN (Journal of Wetlands Environmental Management, 2013)
This study is aimed to compare the blood cholesterol profile, before and after the measurement of maximum aerobic capacity (VO2max) in the students of Jurusan Pendidikan Olahraga dan Kesehatan (JPOK) pada Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Lambung Mangkurat Banjarmasin.Variables in this study consist of lipid profiles, including total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), triglyceride (TG) and Maximum Aerobic Capacity (VO2max). The concept of VO2max according to Kent(1994:268): â€œmaximum oxygen volume consumed per minute to show total work capacity, or volume per minute relative to body weight (ml/kg.min)â€. Operationally, VO2max referred in this study is the maximum volume of oxygen that can be consumed per minute, as measured at progressive run (Bleep Test).The method used in this study is pre-experimental with one group pretest-posttest design. This design implies that a group of subjects are treated for a specific period and the measurements are taken both pre and post. The results: There are changes in blood cholesterol profile after the measurement of maximum oxygen capacity (VO2max), shown by significant decrease of total cholesterol variable, increased HDL, and decreased LDL. Changes in triglyceridevariable showed no significant decrease despite the statistic differences. Specific HDL sub-class increasing after exercise is a constructive lipoprotein sub-class whereas LDL is destructive lipoproteins sub-class that might damage the body. Therefore, an increase in HDL and decrease in LDL found in this study appears to be advantageous and consequently might alter the risk of coronary heart disease.